Review of growth hormone therapy in adolescents and young adults with Prader–Willi syndrome. Issue 2 (March 2015) - Lucas-Herald, Angela K; Perry, Colin G; Shaikh, M Guftar
<x xml:space="preserve">Abstract</x> Consensus guidelines from the Growth Hormone Research Society Workshop recommend growth hormone therapy in all children with genetically confirmed Prader–Willi syndrome (PWS) in combination with dietary, lifestyle and environmental interventions. As yet, however, there are limited published data regarding the use of growth hormone therapy in adolescents and young adults with PWS. This review focuses on the advantages and disadvantages of growth hormone therapy in this particular group. The risk of complications, challenges with consent for therapy, the need for contraception in females with PWS and the appropriate monitoring required are all factors which must be carefully considered in this challenging patient group. Transition from paediatric to adult services can be difficult for most adolescents, but especially so for PWS adolescents and should be undertaken under the care of experienced paediatric and adult endocrinologists and a multidisciplinary team approach. Further research is, however, still required in the management of PWS patients during adolescence.